DESTINATION BRANDING: BRAND IMAGE OF BUDAPEST - Coronel, Monica (Turisztikai és Vidékfejlesztési Tanulmányok, 2021)
Budapest, as many other destinations around the world, competes every day for attracting new visitors. In this effort, the majority of destinations struggle to create a consistent brand which allows them to differentiate themselves from competitors. Most of them spend huge amounts of money to create original and appealing marketing campaigns. However, during this task, there is often a lack of research on a key part of brand theory, the visitors’ insights about the destination, namely destination image. Budapest has not been the exception and it has been identified a gap in regard to researches about the city image. For this reason, this exploratory research intended to find out the image of Budapest among visitors of the Generation Y before and after the visit. Overall, the findings reveal a positive image of the destination, since many negative stereotypes were broken during the visit. Budapest is perceived as a convenient destination, given its good value and accessibility, but also as a city of contrasts, very welcoming and open. Its main competitors are Prague and Vienna.